Identification of GRIN2D as a novel therapeutic target in pancreatic ductal adenocarcinoma - Jiatong Wang; Chi Hin Wong; Yinxin Zhu; Xiaoqiang Yao; Kelvin K C Ng; Chengzhi Zhou; Ka Fai To; Yangchao Chen (BMC, 2023)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease with a dismal prognosis, and despite significant advances in our understanding of its genetic drivers, like KRAS, TP53, CDKN2A, and SMAD4, effective therapies remain limited. Here, we identified a new therapeutic target GRIN2D and then explored its functions and mechanisms in PDAC progression. Methods We performed a genome-wide RNAi screen in a PDAC xenograft model and identified GRIN2D, which encodes the GluN2D subunit of N-methyl-D-aspartate receptors (NMDARs), as a potential oncogene. Western blot, immunohistochemistry, and analysis on Gene Expression Omnibus were used for detecting the expression of GRIN2D in PDAC. Cellular experiments were conducted for exploring the functions of GRIN2D in vitro while subcutaneous and orthotopic injections were used in in vivo study. To clarify the mechanism, we used RNA sequencing and cellular experiments to identify the related signaling pathway. Cellular assays, RT-qPCR, and western blot helped identify the impacts of the NMDAR antagonist memantine. Results We demonstrated that GRIN2D was highly expressed in PDAC cells, and further promoted oncogenic functions. Mechanistically, transcriptome profiling identified GRIN2D-regulated genes in PDAC cells. We found that GRIN2D promoted PDAC progression by activating the p38 MAPK signaling pathway and transcription factor CREB, which in turn promoted the expression of HMGA2 and IL20RB. The upregulated GRIN2D could effectively promote tumor growth and liver metastasis in PDAC. We also investigated the therapeutic potential of NMDAR antagonism in PDAC and found that memantine reduced the expression of GRIN2D and inhibited PDAC progression. Conclusion Our results suggested that NMDA receptor GRIN2D plays important oncogenic roles in PDAC and represents a novel therapeutic target.